Civil Society and the Legitimation of Global Governance - Aart Scholte, Jan (Journal of civil society, 2007)
This article assesses in what ways and to what degrees civil society activities have advanced the legitimacy of global governance institutions. It is argued that these citizen initiatives have often enhanced the democratic, legal, moral and technical standing of regulatory agencies with planetary constituencies and jurisdictions. However, these benefits do not flow automatically from civil society mobilizations and on the whole are much less extensive than they could be. With a view to greater realization of the potential contributions to legitimacy, the article elaborates recommendations for more, more inclusive, more competent, more coordinated, and more accountable engagement of global governance by civil society organizations.